Policy uncertainty and Bitcoin returns - Imlak Shaikh (Borsa Istanbul Review, 2020)
Bitcoin is the digital currency of the digital economy. This article is an attempt to reveal the effects of policy uncertainty on Bitcoin returns with economic policy uncertainty (EPU) in the US, the UK, Japan, China, and Hong Kong. Furthermore, we also present the results of monetary policy uncertainty (MPU) on the Bitcoin market. The robust estimations from the quantile regression and Markov regime-switching model show that Bitcoin returns are affected by EPU. One of the essential findings is that Bitcoin returns are more responsive to EPU in the US, China, and Japan. In the US and Japan, uncertainty has a negative effect on the Bitcoin market whereas in China it has a positive effect. Global MPU uncertainty is also significant in explaining Bitcoin exchange rates. Moreover, the Bitcoin market is negatively affected by uncertainty in Federal Open Market Committee (FOMC), the gross domestic product, and other macroeconomic data. Uncertainty in the equity market and Bitcoin returns are negatively associated.